FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEMERINTAH DESA MELALUI PENGELOLAAN KEUANGAN DESA SEBAGAI VARIABEL INTERVENING - Rulyanti, Dina; Sularso, Raden Andi; Sayekti, Yosefa (BISMA: Jurnal Bisnis dan Manajemen, 2017)
Abstract: This research aimed to empirically analyze the effects of regulation, organizational commitment, communication, and human resources on the performance of the government of the villages in Bondowoso Regency, East Java Province, mediated by the financial management. The sample was 187 respondents consisted of the heads of the villages, secretaries of the villages, heads of the departments, and treasurers. Data were analyzed using Structural Equation Modeling (SEM). Results show that organizational commitment and human resources have significant and positive effects on the financial management and the performance of the village government. However, regulation and communication have no significant effects on the financial management and the performance of the village government. Keywords: Local Government Performance, Village’s Finances, Village’s Financial Management.